FACTORS INFLUENCING NON-BPJS PATIENTS CHOICE OF HOSPITALS FOR OUTPATIENT SERVICES - Rini, Kartika; Setijowati, Nanik; Aminingrum, Rahmawati (Universitas Brawijaya, 2025)
Non-BPJS patients have greater autonomy in selecting healthcare providers, making them a vital segment in ensuring the sustainability and growth of hospital businesses. These patients tend to consider various factors when choosing healthcare services, including accessibility, service quality, hospital reputation, medical technology, and overall patient experience. This study aims to identify the key factors influencing the decision of non-BPJS patients to return to a private hospital for further treatment. By highlighting the importance of this patient segment, the study emphasizes how hospitals can better understand and respond to patient preferences in order to enhance competitiveness. A qualitative research design was employed, with data collected through in-depth interviews involving 10 outpatients from specialist clinics at a private hospital in Malang City. The data were analyzed using thematic analysis, whereby the interview findings were categorized according to emerging themes aligned with the research objectives. The study reveals that, based on patient experiences, several key factors influence the decision of non-BPJS patients to return for services at private hospitals. Among the primary considerations for revisiting outpatient specialist clinics in Malang City are the friendliness of specialist doctors, the availability of medication delivery services, the hospital’s proximity, and affordable medical fees. Conversely, several issues were identified that could negatively impact patient satisfaction if not addressed. These include the lack of clear registration instructions, particularly for new patients; unfriendly behavior from some staff members; cramped facilities; limited patient waiting areas; and prolonged waiting times.